Upaya Penegakan Hukum Pidana Terhadap Tindak Pencurian Diangkutan Umum Yang Meresahkan Masyarakat - Depi Yohana Manurung, Rani Oktavia Purba, Reh Bungana Beru Perangin-Angin, Maulana Ibrahim, Tessa Lo (Mediation : Journal of Law, 2023)
Theft is a crime of property of goods, theft should be considered as damage to someone else's property and by breaking the law you also gain benefits for yourself. Theft committed at night is classified as a crime with aggravating circumstances, so it faces a more serious crime than ordinary theft. Crime is currently increasing very significantly. This growth is not only quantitative but also qualitative. Criminal law as a “tool”; Ultimately, crime prevention and control is expected to function optimally for protection. society for criminals. The actions of law enforcement officials, in this case the police, are really needed by the community. Apart from that, the use of appropriate punishment as a means of eradicating crime also has an impact on increasing crime, which also has an impact on the welfare of society. To defeat the crime of theft with violence. can be implemented in a controlled, managed and responsible manner, the regulations required by law and their implementation are in line with the development of Indonesian society in line with Pancasila and the 1945 Constitution.